2021
DOI: 10.3390/polym13132176
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Novel Cellulose Composites Obtained in 1-Ethyl-3-methylimidazolium Chloride Used as Drug Delivery Systems

Abstract: Two polysaccharides (cellulose and chitosan) and polyurethane dissolved in 1-ethyl-3-methylimidazolium chloride represented the matrix for the obtainment of new composite formulations comprised of lignin, ferrite–lignin hybrid and ketoconazole. The mechanical performances (Young’s modulus and compressive strength) increased with the filler addition. The nature of the filler used in the studied formulations influenced both bioadhesion and mucoadhesion parameters. It was found that the incorporation of lignin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The pores are round and slit-like. The elasticity (ability of material to return to its original for and size after removal of deformation force) is very important property of soft drug formulations and cosmetic products [25][26][27]. As is known, the compression Young's moduli characterize a material's stiffness.…”
Section: Resultsmentioning
confidence: 99%
“…The pores are round and slit-like. The elasticity (ability of material to return to its original for and size after removal of deformation force) is very important property of soft drug formulations and cosmetic products [25][26][27]. As is known, the compression Young's moduli characterize a material's stiffness.…”
Section: Resultsmentioning
confidence: 99%
“…According to V. Bartůněk et al, the recorded magnetic behavior makes cobalt ferrite–lignin hybrids promising candidates for medicinal applications [ 49 ]. Some authors [ 50 , 51 ] confirmed that ferrite lignin delays the release of ketokonazole from a polysaccharide-polyurethane matrix. Dai et al reported [ 52 ] on the synthesis of lignin nanoparticles and their further use as a green carrier for the sustained release of Resveratrol ® .…”
Section: Resultsmentioning
confidence: 99%
“…An initial force of 0.1 N was applied before performing each measurement. The cross-head speed was 1 mm × min −1 , while the applied force was fixed at 20 N. The compressive stresses (σ, kPa), strains (ε), and elastic moduli (G, kPa) were evaluated at room temperature following the procedure previously published in [ 51 , 52 ].…”
Section: Methodsmentioning
confidence: 99%